A Bounded and Incremental Design Approach to Public Administration:30 Years after Shangraw and Crow’s Revolutionary Approach - Lihua Yang (Transylvanian Review of Administrative Sciences, 2022)
Design is a living phenomenon of public administration, but it has not been thoroughly studied by students of public administration (PA). Based on the pioneering work by Simon in 1969, Shangraw and Crow set forth an approach to intellectual activity about public administration that they presented as a design science approach in 1989. This article explores the reasons for the faltering development of this revolutionary approach, proposes a new bounded and incremental design approach to public administration, and analyses the approach’s basic characteristics and six relevant ideas as well as the main research content and courses of public administration and some recommendations for PA practitioners under this new approach.